THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF TEACHING FAIRY TALES IN THE FORMATION OF STUDENTS’ COMMUNICATIVE COMPETENCIES - Riymbayeva Umida (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the theoretical and methodological foundations of teaching fairy tales in forming students’ communicative competencies. The role of fairy tales in speech development, methodology of forming communicative skills, and modern pedagogical approaches are examined based on international experience.